2017
DOI: 10.21697/sp.2015.15.01.01
|View full text |Cite
|
Sign up to set email alerts
|

Zdolności Emocjonalne Kobiet I mężczyzn A stosowane Strategie Radzenia Sobie Ze Stresem

Abstract: STRESZCZENIEW niniejszym badaniu poszukiwano związku między dwiema zdolnościami emocjonalnymi (rozpoznawaniem i rozumieniem emocji) a strategiami radzenia sobie ze stresem, stosowanymi przez kobiety i mężczyzn. Analizy przeprowadzono na grupie 228 osób dorosłych (109 kobiet i 119 mężczyzn) w wieku 18-58 lat (M wieku = 27,46 lat). Strategie radzenia sobie ze stresem mierzono kwestionariuszem COPE, do pomiaru zdolności emocjonalnych wykorzystano natomiast testy SIE-T i TRE. Uzyskane wyniki wskazały na istnienie … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
1
2
0
1
Order By: Relevance
“…These findings were subsequently supported in a study by Strelau et al [36], where the task-oriented style correlated positively with briskness, perseverance, sensory sensitivity, and activity, the emotion-oriented style was negatively related to briskness, endurance, and activity and positively with perseverance, and the likelihood of using an avoidance-oriented style increased with an increase in perseverance and activity. Our study did not show the mediating role of the avoidance-oriented style in the relationship between temperamental traits and occupational burnout, which also corresponds with earlier research [27,36]. The absence of a mediating effect of the avoidance-oriented style in the relationship between temperamental traits and occupational burnout was also found in a study conducted on a sample of psychiatric nurses by Brudek et al [37] which was explained as stemming from weaker links of temperamental traits with this way of responding to difficult situations.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These findings were subsequently supported in a study by Strelau et al [36], where the task-oriented style correlated positively with briskness, perseverance, sensory sensitivity, and activity, the emotion-oriented style was negatively related to briskness, endurance, and activity and positively with perseverance, and the likelihood of using an avoidance-oriented style increased with an increase in perseverance and activity. Our study did not show the mediating role of the avoidance-oriented style in the relationship between temperamental traits and occupational burnout, which also corresponds with earlier research [27,36]. The absence of a mediating effect of the avoidance-oriented style in the relationship between temperamental traits and occupational burnout was also found in a study conducted on a sample of psychiatric nurses by Brudek et al [37] which was explained as stemming from weaker links of temperamental traits with this way of responding to difficult situations.…”
Section: Discussionsupporting
confidence: 93%
“…The results attest to mediational relations between temperament and coping with stress -the way an individual behaves in difficult situations is determined not only by the properties of the stressor but also by the individual's personal capacity for the neurobiological processing of stimulation. The authors who have written about the positive correlations of emotional reactivity and perseverance with emotionoriented style include Jachnis [27], who discussed the impact of temperament on coping styles in university students. Similar conclusions were reached by Heszen [32], whose research on the significance of temperament in stressful situations demonstrated that emotional reactivity and perseverance increased the tendency to use strategies focused on reducing negative emotions (in the case of perseverance there was also a correlation with avoidance-oriented strategies, which was not supported in the present study), whereas briskness, endurance, and activity favor the appraisal of situations as challenges.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Występowanie opisywanego związku jedynie u osób płci żeńskiej może wynikać z ogólniejszych różnic międzypłciowych w obszarze radzenia sobie. Jak już wskazano, zgodnie z niektórymi wynikami badań kobiety ogólnie częściej przejawiają styl Poszukiwania wsparcia (Graves i in., 2021;Piekarska, 2015;Ptacek i in., 1994;Matud, 2004). Różnica ta ujawniła się również w przeprowadzonym badaniu.…”
Section: Dyskusjaunclassified